Using an integrated model of the theory of planned behavior and the temporal self-regulation theory to explain physical activity in patients with coronary heart disease - Wang, Wenqin; Wu, Minjuan; Hua, Yun; Zhang, Xingwei; Feng, Guohe (Frontiers in Psychology, 2023)
Background: This study aimed to explore the psychosocial determinants of PA levels in patients with coronary heart disease (CHD) using an integrated theoretical model based on the theory of planned behavior (TPB) and the temporal self-regulation theory (TST). Method: This was a prospective study conducted at the Affiliated Hospital of Hangzhou Normal University in Zhejiang, China. A total of 279 patients with CHD (176 men, aged 26 to 89 years; M = 64.69; SD = 13.17) were selected for study inclusion by convenience sampling. Data on attitude, subjective norm (SN), perceived behavioral control (PBC), and intention for the TPB model and consideration of future consequences (CFC), habit, and self-control (SC) variables for the TST model were collected when participants were 1-2 days before discharge (Time 1, T1), and a telephone follow-up was made to assess the participants’ self-reported PA levels one week after their discharge (Time 2, T2). Results: The results revealed that only 39.8% of patients with CHD met the guideline recommendations on PA. Data analyses using structural equation modeling (SEM) in Mplus 8.3 showed that in the simple mediation model, attitude, PBC, and CFC were positively related to intention to practice the guideline-recommended level of PA. However, SN was not. In addition, intention was shown to mediate the relationships between attitude, PBC, CFC, and PA levels. Furthermore, based on the moderated mediating model, intention and habit were shown to be positively associated with PA levels. However, SC was not. Moreover, SC played a significant moderating role between intention and PA levels. However, habit strength did not moderate the relationship between intention and PA levels. Conclusions: An integration of the TPB and TST models offers a good theoretical tool for understanding PA levels in patients with CHD.